Tugas dan Wewenang Otoritas Jasa Keuangan (OJK) Dalam Mengawasi Sektor Keuangan di Indonesia - Rosita, Dita Puspa; B, Baidhowi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Financial Services Authority (OJK) is an independent institution established under Law Number 21 of 2011. Its primary purpose is to implement an integrated system of regulation and supervision over all activities within the financial services sector. This study employs a normative legal research method through literature review and document analysis. The findings indicate that OJK's main duties include regulating, supervising, inspecting, and investigating activities across the financial services sector, which covers banking, capital markets, and non-bank financial institutions. OJK’s authority includes formulating policies, granting business licenses, monitoring compliance, and protecting the rights of consumers in the financial services industry.